If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -1y) + -1(x + y) = 0 Remove parenthesis around (x + -1y) x + -1y + -1(x + y) = 0 x + -1y + (x * -1 + y * -1) = 0 x + -1y + (-1x + -1y) = 0 Reorder the terms: x + -1x + -1y + -1y = 0 Combine like terms: x + -1x = 0 0 + -1y + -1y = 0 -1y + -1y = 0 Combine like terms: -1y + -1y = -2y -2y = 0 Solving -2y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '-2'. y = 0 Simplifying y = 0
| (8m+6n)-(7m-5n)= | | 24=3/4y | | -12x+5y=17 | | x+2.6x=180 | | 2x=15-y | | (6m+2np)-(3m-5np)= | | -0.5+y=6x | | (x+3)12=8(4x-5) | | 7c-9=9+7c | | 9x+13=3+9x | | 30+5y=30+5y | | x=(-10)-8 | | (4x-2)^-2/3=0 | | -4x-41=28-4x | | y=5x^2-4x-7 | | Y=ln(3x^2-4x) | | 2x^2-22=12x | | 13y+3x=110 | | 50-9.8t^2/2 | | 3x+13y=110 | | 6x+12y=8936 | | m=24-3 | | 3x^2-7=101 | | -3/7x-1/7 | | 2x+4y=422 | | Lne^4x=12 | | tan(3x+5)=4 | | x^2+12x+20=9 | | 2x^2-5=-18 | | x^2-12x-20=9 | | 7m-5-3m= | | a+2x=3-ax |